How can an English teacher adapt the lessons in order to meet the needs of students with different proficiency levels in class? (2018)
ABSTRACT: This paper presents an Action Research study on the implementation of three strategies in order meet students needs with different proficiency levels in class. It was carried out at Colegio Theodoro Hertzl in eighth grade. The data was collected through class observations, students log and a survey. Three strategies were the basis to design the action plan. It was mandatory to identify learning styles in order to match how students learn and teaching methods. According to Ellis (1989), once teachers become aware of their learners learning styles, they may help them more efficiently by increasing their amount of learning as a result of identifying their strengths and weaknesses. Later on, Differentiated Instruction was implemented to include all students. The methodology implemented will be the creation of learning profiles of each student containing pertinent information about learning preferences, favorite hobbies and interests. Lora Robinson, Ed.D. Nancy Maldonado, Ph.D. Jerita Whaley, Ed.D (2014) claims that the absence of differentiated instruction in many classrooms hinders success for students who do not learn the same way as their peers. Last, Collaborative Learning to increase engagement and confidence. The teacher will focus on Promoting social interaction by Collaboration, Cooperation, and Group Work. The results showed that when teachers know how their students learn, it allows to design different activities based on student´s interest. Furthermore, teachers should design diverse activities that involves challenge offering different alternatives to reach the goal. Finally, the teacher should propitiate the interaction with others that allows a meaningful learning. The flexibility of the activities permits high proficient learners to explore new advanced abilities and low proficient learner to learn from those.